2010
DOI: 10.2151/jmsj.2010-305
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variations in Lower-Tropospheric Wind over Japan Part I: Observational Results using the Wind Profiler Network and Data Acquisition System (WINDAS)

Abstract: This study investigates diurnal variations in lower-tropospheric wind over Japan during [2002][2003][2004][2005][2006][2007][2008] using data from 31 stations of the Wind profiler Network and Data Acquisition System (WINDAS) and the Automated Meteorological Data Acquisition System (AMeDAS). The diurnal and semidiurnal components are extracted and analyzed to identify the dominant processes for each height range and for each season. Near the surface, the diurnal component is controlled by local wind systems (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…Thus, a comprehensive understanding of diurnal variations in the tropopause and the stratosphere is important. However, as noted by Sakazaki and Fujiwara [2010a, 2010b] (hereafter referred to as SF10a and SF10b, respectively), there are relatively few previous studies on diurnal variations particularly below ∼20 km in the midlatitudes; these studies are briefly summarized in the following paragraphs. This lack of reports is mainly because only a few subdiurnal upper air measurements have been conducted in the troposphere and the lower stratosphere.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Thus, a comprehensive understanding of diurnal variations in the tropopause and the stratosphere is important. However, as noted by Sakazaki and Fujiwara [2010a, 2010b] (hereafter referred to as SF10a and SF10b, respectively), there are relatively few previous studies on diurnal variations particularly below ∼20 km in the midlatitudes; these studies are briefly summarized in the following paragraphs. This lack of reports is mainly because only a few subdiurnal upper air measurements have been conducted in the troposphere and the lower stratosphere.…”
Section: Introductionmentioning
confidence: 69%
“…Two studies, SF10a and SF10b, recently investigated diurnal wind variations in the lower troposphere (below ∼5 km) over Japan, predominantly using data from 31 stations of the wind profiler network in Japan (WINDAS) and from five analysis/reanalysis data sets. The authors found that the diurnal wind component was caused by at least four (not two) different phenomena: (1) local wind systems, (2) diurnal eastward moving eddies, which propagate eastward with a horizontal wavelength of ∼1500 km and a zonal phase speed of 10 to 15 m s −1 , (3) medium‐scale waves, and (4) atmospheric tides.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a companion paper, Sakazaki and Fujiwara (2010; hereafter referred to as SF10) investigated diurnal variations in lower tropospheric wind over Japan, using a 6-year data set obtained by the Wind profiler Network and Data Acquisition System (WINDAS) in Japan. The authors examined the characteristics of diurnal and semidiurnal components of zonal wind (u) and meridional wind (v) for each height range and for each season.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, previous surface wind analyses in central Japan using AMeDAS data (e.g., Suzuki and Kawamura 1987) mostly reflect the land-sea and mountain-valley circulations along the valleys. Recently, the JMA wind profiler network has detected diurnal wind components in the lower troposphere, and the contribution of return currents of the local wind system was investigated at the 1-to 3-km level (Sakazaki and Fujiwara 2010). To assess the influence of global warming on environmental changes in the Japanese Alps region, an inter-university cooperative project (JALPS) was established in 2010 at the University of Tsukuba, Shinsyu University, and Gifu University.…”
Section: Introductionmentioning
confidence: 99%